Malondialdehyde, Selenium & α-Tocopherol in Kidney Stones - Maria Kazi, Sumayya Kazi, Qamar Zaman Phull, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objectives: To determine role of a-tocopherol and selenium and evaluate malonadehyde in calcium stone of kidney. Study Design: Case-control study. Place & Duration: Department of Biochemistry. Isra University and Hi-tech Laboratory University of Sindh, Jamshoro July 2013- January 2014. Material & Methods: Malondialdehyde (NIDA). a-tocopherol (a-TP) and Selenium were measured by using spectrophotometeric methods by commercially available kits. Resiut: Mean= SD of MDA was noted as 26.0337.84171.tmolil versus 1.8820.621).tmol.:1 in the cases and controls (p=0.001). The a-tocopherol la-TP) was low in concentration in the cases compared to controls i.e. 0.38±0.1-16ing/d1 VS, 1.06±0.169 m2/d1(p=0.001). Selenium in cases and controls was found as 38.4± 14.10[igil vs. 84.5± I 0.22pg/d1 respectively. it showed severe defic ienc-y in cases. (13=0.001 ). Conclusion: Present study reports low Levels ofa-tocopherol and selenium in the subjects with renal stone. and lipid peroxidation plays major role in the pathogenesis of calc him stone of kidney.